A continuous times-series and discrete measure analysis of two individual divers performing the 3½ pike somersault dive. Issue 2 (1st February 2023) - Walker, Cherie; Warmenhoven, John; Sinclair, Peter; Cobley, Stephen
ABSTRACT: Springboard diving training is often focused upon skill repetition to establish movement accuracy, stability and consistency. Within-participant study designs provide the ability to understand how individuals create these skills under different movement strategies. IMUs measured angular velocity time-series data of two athletes performing multiple repetitions of forward 3½ somersault pike dives. Functional Principal Component Analyses ( f PCA) were performed to examine individual movement structure and variability. The first five f PC's represented approximately 98% of the variability in angular velocity for both divers. To determine the relative importance of angular velocity variability, Pearson's correlations for pairwise comparisons were used to assess the relationship between f PC scores and discrete performance variables during takeoff, flight and entry. Divers exhibited a different number and types of significant correlations (International = 4; National = 11). Only one correlation was common for both divers; higher angular velocity during Initial Flight and/or Somersault phases resulted in more vertically aligned entry posture (International: f PC1 r = −0.761, p < 0.05; National: f PC3 r = −0.796, p < 0.01). Findings identify individualised angular velocity time-series structure and kinematic performance variables (International = angular; National = linear) that can be used by coaching/sport science teams to optimisation performance success.